Teoremas de Maschke - Santos, Ricardo Leite dos (2013)
In representation theory, having a representation of a group G is equivalent to having a kG-module. Since |G-modules which are sums of irreducible kG-modules form a very important class in the theory of modules, to know conditions for a kG-module be irreducible or completely reducible from the particularities of the field k and the group G become a very important issue, whose solution was originally presented by the German mathematician Heinrich Maschke which proved that if the order of G is not a multiple of the characteristic of the field k, then kG is completely reducible (or semisimple). From there, issues unrelated to representation theory, but that concern the semisimplicity of cross products in general are treated as Maschke-type theorem. Our goal in this dissertation is to present some versions of this theorem, starting with classic versions involving cross products for actions of groups on algebras and then versions for Hopf algebras and smash products.